Motor cortex tDCS does not improve strength performance in healthy subjects - Rafael Montenegro; Alexandre Okano; Jonas Gurgel; Flávia Porto; Felipe Cunha; Renato Massaferri; Paulo Farinatti (Universidade Estadual Paulista (UNESP), 2015)
The influence of transcranial direct current stimulation (tDCS) upon maximal strength performance in exercises recruiting large muscle mass has not been established in healthy populations. The purpose of this study was to investigate whether anodal tDCS was able to increase the performance during maximal strength exercise (MSEX) in healthy subjects. Fourteen volunteers (age: 26 ± 4 yrs) performed two MSEX after anodal or sham tDCS (2mA; 20min prior MSEX), involving knee extensors and flexors in concentric isokinetic muscle actions of the dominant limb (3 sets of 10 repetitions). The electrical muscle activity (sEMG) of four recruited muscles was recorded during MSEX. Anodal tDCS was not able to improve force production (i.e., total work and peak torque), fatigue resistance, or electromyographic activity during MSEX when compared to sham condition. In conclusion, anodal tDCS applied upon the contralateral motor cortex was not capable of increasing the strength performance of knee extensors and flexors in young healthy subjects.